2008
DOI: 10.1080/03079450802216637
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantibiotic susceptibility of DutchMycoplasma synoviaefield isolates originating from joint lesions and the respiratory tract of commercial poultry

Abstract: The in vitro susceptibility of 17 Dutch Mycoplasma synoviae isolates from commercial poultry to enrofloxacin, difloxacin, doxycycline, tylosin and tilmicosin was examined. Three isolates originated from joint lesions and 14 were from the respiratory tract. The type strain M. synoviae WVU 1853 was included as a control strain. Antibiotic susceptibility was tested quantitatively using the broth microdilution test. Based on initial and final minimum inhibitory concentration values, all tested isolates were suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 18 publications
4
42
3
Order By: Relevance
“…During the past decade, a limited number of studies relating to the in vitro susceptibility of M. synoviae field strains have been published (8,(15)(16)(17)(18), and in one case, two M. synoviae isolates resistant to En were identified (8). In contrast, the results of this study reveal a high percentage (50%) of M. synoviae field isolates resistant to En.…”
Section: Discussioncontrasting
confidence: 63%
“…During the past decade, a limited number of studies relating to the in vitro susceptibility of M. synoviae field strains have been published (8,(15)(16)(17)(18), and in one case, two M. synoviae isolates resistant to En were identified (8). In contrast, the results of this study reveal a high percentage (50%) of M. synoviae field isolates resistant to En.…”
Section: Discussioncontrasting
confidence: 63%
“…sp. 1220 (MIC 50 2 μg/ml and MIC 90 4 μg/ml) and other Mycoplasma species of poultry [3, 13, 20, 21]. In addition, the increasing occurrence of quinolone-resistant M. synoviae and M. gallisepticum field isolates were also observed [13, 22].…”
Section: Discussionmentioning
confidence: 99%
“…1220 (MIC 50 2 μg/ml and MIC 90 4 μg/ml) and other Mycoplasma species of poultry [3, 13, 20, 21]. In addition, the increasing occurrence of quinolone-resistant M. synoviae and M. gallisepticum field isolates were also observed [13, 22]. In the current study, the detected MIC 50 values (5 μg/ml for enrofloxacin, 10 μg/ml for difloxacin and ≥10 μg/ml for norfloxacin) were even higher than the ones reported before [3, 13, 2022], confirming the observation of increasing quinolone-resistance in Mycoplasma species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and field studies showed that oxytetracycline was effective against M. synoviae (Landman et al, 2008) and M. synoviae-induced EAA (Feberwee et al, 2009). However, due to the temporary effect of antibiotic treatment and the risk of residues in eggs for consumption, alternative strategies such as vaccination should be considered for the control of M. synoviae-induced EAA.…”
Section: Introductionmentioning
confidence: 99%